Os componentes da variância da taxa de crescimento da firma - Brito, Luiz Artur Ledur (2005)
One of the main characteristics of strategy as a field of research is its focus on the individuality of firms in contrast with economics where the focus moves to the industry. Firms differ in several dimensions and these differences constitute the essence of the research interest in strategy. One of these dimensions is the rate at which firms increase or decrease in size – firm growth. This dissertation analyzed the structure of variability of firm growth rates with the objective of identifying groups of factors that determine this variability and its relative influence. The research was done using an international sample of 13,221 firms, from 47 countries and 216 industries during the period of 1994 to 2002. Data was obtained from the Compustat Global database, maintained by Standard and Poor’s. The raw data was made comparable by accounting for inflation and currency changes using indexes form the World Bank Development Indicators. The variance components technique, normally used in field such as genetics and biology to study the naturally occurring variability, was used to understand the variance composition of firm growth rates. The main finding was that individual, idiosyncratic factors of each firm are responsible for the greatest portion of explained variance. Firm effects dominate the explanation of observed variance while country and industry effects have shown a much smaller influence. The predominance of firm effects has relevant theoretical implications. First, it offers a strong support to the approach of Penrose (1959) to firm growth, who considered growth as a natural, endogenous process, deriving from the use of firm specific resources. It can also be used to question the relevance of some economic approaches to firm growth that prioritize effects associated to industry like industry evolution and concentration. This connection between firm growth and individual firm resources also allows one to see growth as an additional dimension of competitive advantage linking this research with the resource-based view of strategy (RBV). One of the managerial implications of this finding relates to the efficacy of public policies to promote firm growth. Industry effects were found to be generally small, often smaller than country effects. Public policies targeted at industry level may then be affecting a less significant source of variation in firm growth rates. The results suggest that policies targeted at the individual firm level, and their individual resources may be much more effective in promoting growth. Even policies that address country infrastructure, like health, education, transport may be more effective than industry oriented policies due to the higher relevance of country effects in relation to industry effects in most cases. Besides its main contribution, the study also explored several other aspects about growth rates and their variability allowing several secondary conclusions.